Quality control and microbial analysis of liquid herbal drug formulations marketed in three major cities of South Eastern Nigeria - Michael Onyeukwu; Emmanuel Uronnachi; Chidalu Ikeotuonye; Chibuzor Ijezie; Tochukwu Okeke; Somto Ewuzie; Ifeanyi Nzekwe (Journal of Preventive and Complementary Medicine)
Background: The use of herbal drugs is on the rise in Nigeria and globally, raising concerns about product adulteration and unverified therapeutic claims made by manufacturers.Objectives: This study aimed to evaluate the quality of liquid herbal drugs marketed as having antimicrobial properties in three major markets in South Eastern Nigeria. The focus was on their physicochemical properties, microbial content, toxicity, and antimicrobial efficacy.Methods: A total of 45 liquid herbal drug samples from five popular brands (collected in triplicates) were obtained from three major drug markets in South Eastern Nigeria. Microbial load was assessed using surface viable count and pour plate methods. Acute toxicity was evaluated using Lorke’s method, while antimicrobial activity was determined through the agar well diffusion method.Results: None of the samples exhibited acute toxicity; however, only 35.6% contained microbial loads within acceptable limits. Isolated bacterial species included Staphylococcus aureus (33.33%) and Escherichia coli (26.66%), among others. Fungal species identified were Microsporum spp. (4.44%) and Penicillium marneffii (2.22%). Significant labeling irregularities were noted, including omissions of NAFDAC numbers, batch numbers, and active ingredients. Approximately 53% of the samples demonstrated no antimicrobial activity against common microorganisms (Candida albicans, E. coli, and S. aureus), contradicting their labeled claims.Conclusion: The findings highlight a lack of regulation and standardization in the production of liquid herbal products, posing substantial health risks to consumers.